2016
DOI: 10.1186/s12884-016-0798-y
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of care by a primary midwife (caseload midwifery) increases women’s satisfaction with antenatal, intrapartum and postpartum care: results from the COSMOS randomised controlled trial

Abstract: BackgroundContinuity of care by a primary midwife during the antenatal, intrapartum and postpartum periods has been recommended in Australia and many hospitals have introduced a caseload midwifery model of care. The aim of this paper is to evaluate the effect of caseload midwifery on women’s satisfaction with care across the maternity continuum.MethodsPregnant women at low risk of complications, booking for care at a tertiary hospital in Melbourne, Australia, were recruited to a randomised controlled trial bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
113
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(136 citation statements)
references
References 18 publications
(41 reference statements)
12
113
1
10
Order By: Relevance
“…Becoming self‐aware of one's sleep status, rather than ignoring the presence of sleepiness and sleep deprivation, may require a significant cultural shift in the mindset of many midwives . There has been some debate within the midwifery community regarding the delivery of continuity or caseload care (a single midwife providing all prenatal, intrapartum, and postpartum care) versus team‐based midwifery care (continuity of midwifery care shared between practice partners) . Although some midwives consider continuity of midwifery care to only be care provided by a single provider, others believe that continuity of care may also be achieved by working closely with other care partners .…”
Section: Discussionmentioning
confidence: 99%
“…Becoming self‐aware of one's sleep status, rather than ignoring the presence of sleepiness and sleep deprivation, may require a significant cultural shift in the mindset of many midwives . There has been some debate within the midwifery community regarding the delivery of continuity or caseload care (a single midwife providing all prenatal, intrapartum, and postpartum care) versus team‐based midwifery care (continuity of midwifery care shared between practice partners) . Although some midwives consider continuity of midwifery care to only be care provided by a single provider, others believe that continuity of care may also be achieved by working closely with other care partners .…”
Section: Discussionmentioning
confidence: 99%
“…7 The World Health Organization includes standards for improving quality care in health facilities such as effective and respectful communication that responds to women's needs and preferences, and the provision of sensitive emotional support. 13 As part of the M@NGO trial, we explored women's views across the entire spectrum of pregnancy and birth using specifically designed questionnaires offered at 36 weeks of pregnancy, 6 weeks and 6 months postpartum. 9 Although the Cochrane review on midwife-led continuity of care did not include a meta-analysis of women's experiences, most of the included studies reported a higher rate of maternal satisfaction in midwife-led continuity models of care.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers also seem to need some continuity in their contact with health professionals; they would like to address the same person from the beginning of pregnancy to the end of the postpartum period. This need for continuity has already been shown in several studies [23-26]. In practice, parents and professionals think that the solutions should be accessible to everyone and be available at all times.…”
Section: Discussionmentioning
confidence: 89%